Analysis of the Utilization of Digital Media as a Means of Public Communication: A Case Study at the Cattleya Mental Health Center - Sandi, Yoki Famila (Open Access Indonesia Journal of Social Sciences, 2023)
Digital media has affected various aspects of life, including in the field of mental health. Mental health services are an important part of efforts to improve the quality of life of individuals and society as a whole. By analyzing the use of digital media as a means of public communication in mental health services, it is hoped that useful insights and recommendations can be found to improve access, quality, and the positive impact of mental health services in this digital era. This research is qualitative research that explores and describes in detail a situation or phenomenon of the research object studied by developing concepts and gathering existing facts. Raw data is analyzed and organized by data collection date, data source, data type, data description, and data nature. All data must be read in order to find out what data has been obtained, the source of the data, and its meaning. Through this platform, individuals can access information about various mental disorders, stress management, relaxation techniques, and other resources that can help them deal with mental health problems. In addition, digital media can also provide discussion forums and community support for individuals experiencing mental health problems. Through online discussion groups, community forums, or social media channels, individuals can share experiences, get emotional support, and feel that they are not alone in their struggles. Interaction with others who are experiencing similar problems can increase self-understanding, strengthen a sense of hope, and provide inspiration for recovery.